Interspecific relationships of tardigrades with bacteria, fungi and protozoans, with a focus on the phylogenetic position of Pyxidium tardigradum (Ciliophora). (December 2016) - Vecchi, Matteo; Vicente, Filipe; Guidetti, Roberto; Bertolani, Roberto; Rebecchi, Lorena; Cesari, Michele
Abstract : Symbiosis can be defined as an interaction between individuals of different biological species. Despite the small number of studies solely devoted to symbiotic interactions between tardigrades and micro‐organisms (such as bacteria, fungi and protozoans), numerous reports can be found in the literature, especially as notes in faunal and alpha‐taxonomy studies. Here, we review the literature and compile a list of the interactions between tardigrades and micro‐organisms, excluding those that constitute food for tardigrades. Furthermore, a genetic study on a tardigrade symbiophoront, the ciliate Pyxidium tardigradum van der Land, 1964 was performed. There are a few records of P. tardigradum on both European and Asian tardigrades, but no morphological discrepancies among populations have been observed. We present here the phylogenetic positioning for P. tardigradum inferred by using nuclear ribosomal markers (18S and 5.8S). The phylogenetic trees showed all P. tardigradum specimens grouped together, and belonging to the family Operculariidae, order Operculariida. Moreover, a study based on the genetic distances between a Portuguese and an Irish population of P. tardigradum was performed using internal transcribed spacers ITS1 and ITS2. The ITS1 and ITS2 sequences showed differences between populations, leading us to hypothesize the presence of cryptic species.